Control of vaccine preventable diseases in Australian infants: reviewing a decade of experience with DTPa-HBV-IPV/Hib vaccine. Issue 1 (2nd January 2021) - Bayliss, Julianne; Nissen, Michael; Prakash, Damita; Richmond, Peter; Oh, Kyu-Bin; Nolan, Terry
ABSTRACT: The combined vaccine against diphtheria, tetanus, pertussis, hepatitis B, poliomyelitis, and Haemophilus influenzae b (DTPa-HBV-IPV/Hib, Infanrix Hexa, GSK) has been used for childhood immunization in Australia according to a two-, four-, six-month schedule since 2009. We reviewed data available in the Australian National Notifiable Diseases Surveillance System, annual vaccination coverage reports, the Database of Adverse Event Notifications, and peer-reviewed literature to assess vaccine coverage rates, incidence of all six vaccine preventable diseases, and the safety profile of DTPa-HBV-IPV/Hib vaccine in Australian infants over a period of ten years of exclusive use. Between 2009 and 2018 vaccine coverage for infants aged 12 months increased from 91.7% to 94.0% and from 84.9% to 92.6% for all and for Indigenous infants, respectively. Over the same time period, there were no reports of poliomyelitis, diphtheria or tetanus in infants <12 months of age. The incidence of hepatitis B among Australian infants <12 months of age remains 10 to 20-fold lower than the national average. Control of Haemophilus influenzae b (Hib) and pertussis disease has continued to be challenging. Timely administration of the primary series, as well as increasing coverage rates, particularly among Indigenous children, has contributed to improvements in Hib and pertussis disease control. The incorporation of additional strategies such as adjustment of the first vaccination encounter to six weeks of age, parental cocooning, and most recently maternal vaccination has further reduced the burden of pertussis, particularly during the first six months of life. The frequency of the ten most common adverse events related to the DTPa-HBV-IPV/Hib vaccine demonstrates an acceptable safety profile. Data collected over ten years of consistent, exclusive use of the DTPa-HBV-IPV/Hib vaccine in Australia highlights combination vaccination as a cornerstone in maintaining infant health. PLAIN LANGUAGE SUMMARY: What is the context? Infanrix hexa is a vaccine protecting against six childhood diseases: diphtheria, tetanus, pertussis (whooping cough), hepatitis B, polio, and Haemophilus influenzae type b (Hib). All Australian children should receive the vaccine at two, four, and six months of age, as per national recommendation. What is new? We reviewed the impact of Infanrix hexa in the national immunization program between 2009 and 2018, assessing vaccine coverage rates and notifications of disease. We found that: No cases of polio, diphtheria or tetanus occurred in Australian infants under one year of age. Hepatitis B and Hib notifications remained uncommon in under-one-year-old infants with only few cases reported annually during the decade. Maternal immunization and first dose administration at six weeks of age have reduced pertussis incidence in infants under two months of age. What is the impact? Infanrix hexa is the cornerstone of the Australian infant immunization program, providing sustained protection against six childhood diseases since 2009. Maternal immunization and administration of the first vaccine does as early as early as six weeks are beneficial for the protection of the most vulnerable population, i.e. new-borns.